Factor Structure and Model Validation of Emotional Intelligence: An Exploratory and Structural Equation Modeling Approach - V, Soumya; K, Santhos Kumar (Journal of Nepal Commerce Association, 2025)
The present study examined the level of emotional intelligence among higher secondary students in the Kottayam district using a descriptive survey research design. An adapted 15-item scale derived from the NHS Leadership Toolkit was administered to a stratified random sample of students from aided and unaided schools. Exploratory Factor Analysis (EFA) confirmed a clear three-factor structure—Self-Awareness, Managing Emotions, and Empathy—with all factor loadings exceeding 0.50. Reliability analysis demonstrated strong internal consistency, with Cronbach’s alpha values ranging from 0.818 to 0.854. The Kaiser-Meyer-Olkin value of 0.816 and significant Bartlett’s test established sampling adequacy. Structural Equation Modeling (SEM) further validated the measurement model, yielding excellent fit indices (CFI = 0.991, GFI = 0.955, TLI = 0.988, RMSEA = 0.040). Regression weights and standardized estimates indicated significant and meaningful relationships among the constructs. The study concludes that the developed instrument possesses strong psychometric properties and is suitable for assessing emotional intelligence among higher secondary learners, providing insights that can guide educational planning and emotional skill development programs.